Tetanus Vaccination in Agricultural Workers: A Retrospective Study on Seroprevalence over 10 Years - Ermanno Vitale; Veronica Filetti; Giorgio Bertolazzi; Gabriele Giorgianni; Nektaria Zagorianakou; Andrea Marino; Massimiliano Esposito; Vincenzo Restivo; Serena Matera; Venerando Rapisarda; Luigi Cirrincione (Vaccines)
Background/Objectives: Tetanus is a serious, non-contagious infection caused by Clostridium tetani, which remains a global health threat despite the availability of an effective vaccine. The current state of immunization for agricultural workers in Italy reveals significant disparities, reflecting a non-homogeneous distribution of vaccination coverage across regions and subgroups. The aim of the study was to investigate the prevalence of tetanus antibodies in a cohort of agricultural workers in Eastern Sicily in order to evaluate possible public health strategies for improving vaccination coverage. Methods: This observational retrospective study assessed tetanus immunization coverage in agricultural workers in Eastern Sicily during the period from 2012–2022. Results: A total of 1143 workers participated, of which 71% (n = 871) had protective tetanus antitoxin levels. Of the 835 vaccinated workers, 9% were not immune, while 19% of those who were not vaccinated or did not recall their vaccination history were immune. Significant gaps in vaccination were noted, particularly among non-European workers, with only 23% vaccinated compared to 89% of European workers. Additionally, vaccination rates were higher in those born after 1963, when vaccination became mandatory. Conclusions: The results underscore the need for targeted vaccination strategies, especially for older and migrant workers, as well as the importance of workplace immunization programs led by occupational physicians. Improving vaccination coverage among agricultural workers is essential for preventing tetanus infections in high-risk agricultural populations.